Pendekatan Gender Dalam Studi Al-Qur’an - Ikrar (LP2M Universitas PTIQ Jakarta, 2018)
The interpretation of verses on gender and feminism in the Koran can be contextualized in accordance with the Koran’s ethical values. but in practice there are several gender approaches in the study of the Koran, thus Muslims tend to see feminism as something that comes from outside that must be responded to. In this case there are 3 groups; Anti-Feminism, arguing that the system of relations between men and women in society is in accordance with the teachings of Islam. Gender and feminism come from the west and are expected to damage the standard Islamic teachings.Pro feminism, which argued that women in general were in a discriminatory patriarchal society system that needs to be reconstructed. All teachings of feminism are congenial with Islamic values. The West is seen as a symbol of progress (modernity), so what comes from the west is considered good. The three groups that Accepting and Rejecting Selectively, this group tent objectify certain matters as what comes from the was can not be considered bad by default, so good things need to be taken. Even gender and feminism have experienced a plurality of streams, so that what is congenial with Islam is accepted and contrary with Islam is rejected. Therefore, it is necessary to reform the interpretation about gender relations that are textual and can be more contextual and harmonious with the ideal values of the holy Koran that are just, egalitarian, and humane.